2005
DOI: 10.1007/s00192-004-1257-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of abdominal sacrocolpopexy with synthetic mesh versus abdominal sacrocolpopexy with cadaveric fascia lata

Abstract: Nineteen women who had an abdominal sacrocolpopexy (ASC) with synthetic mesh and 18 women who had an ASC with freeze-dried, irradiated cadaveric fascia lata returned for blinded pelvic organ prolapse quantification (POPQ) examinations. The mean relative vaginal descent (delta) from perfect total vaginal length in the mesh group was 1.1 (0.3) cm, and the delta in the fascia group was 2.8 (0.8) cm (p=0.02, Mann-Whitney U). The proportion of women with "optimal" surgical outcome in the mesh group was 89% and 61% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…42 This is similar to a retrospective study that compared sacral colpopexy performed with FD-CFL (Community Tissue Services, Portland, OR) or synthetic mesh, Marlex (CR Bard, Cranston, RI) or Mersilene (Ethicon, Somerville, NJ), in 37 patients (19 synthetic mesh and 18 allograft) and found that 61% of patients in the allograft group had optimal outcome as compared with 89% of the patients in the synthetic mesh group with mean follow-up intervals of 21 and 26 months, respectively (P = 0.06). 43 There were no significant adverse events such as erosions from either group.…”
Section: Biologic Graftmentioning
confidence: 82%
“…42 This is similar to a retrospective study that compared sacral colpopexy performed with FD-CFL (Community Tissue Services, Portland, OR) or synthetic mesh, Marlex (CR Bard, Cranston, RI) or Mersilene (Ethicon, Somerville, NJ), in 37 patients (19 synthetic mesh and 18 allograft) and found that 61% of patients in the allograft group had optimal outcome as compared with 89% of the patients in the synthetic mesh group with mean follow-up intervals of 21 and 26 months, respectively (P = 0.06). 43 There were no significant adverse events such as erosions from either group.…”
Section: Biologic Graftmentioning
confidence: 82%
“…The investigators found a significantly higher failure rate in the allograft group (32%) vs the mesh group (9%, P=0.007). Gregory et al found similar anatomical failure rates when comparing mesh (Mersilene or Marlex) to allograft (freeze-dried, gamma-irradiated) [26]. Thus, the literature provides evidence that if given a choice between mesh and allograft in a sacrocolpopexy, in regard to anatomical outcomes, mesh is superior.…”
mentioning
confidence: 71%
“…Allografts come from a human source other than the patient and may include cadaveric fascia or cadaveric dermis; to avoid the complication of vaginal erosion, some surgeons use cadaveric fascia instead of synthetic mesh, but this is associated with a higher rate of prolapse recurrence. 32 Xenografts are biological tissue obtained from a specie foreign to the patient, e.g. porcine dermis or bovine pericardium.…”
Section: Treatment Of Enterocoele or Vault Repairmentioning
confidence: 99%